Instructional media and technologies for learning - Heinich, Robert; Molenda, Michael; Russell, James D.; Smaldino, Sharon E. (Merrill/Prentice Hall, 2002)
Instructioncal Media and Technologies for Learning presents a complete range of media formats in terms of how they can be integrated into classroom instruction using the ASSURE model of lesson planning. Written from the viewpoint of the teacher, the text shows specifically and realistically how media fit into the daily life of the classroom. This book is intended for educators at all levels who place a high value on successful learning. Its purpose is to help them incorporate media and technologies for learning into their repertoire -- to use them as teaching tools and to guide students in using them as learning tools.